Shadow banking activity and entrusted loans in a DSGE model of China - Wang, Chaowei; Mai Le, Vo Phuong; Matthews, Kent; Zhou, Peng (2020)
This paper examines how the risky lending activities of the state‐owned enterprises (SOEs) affect the effectiveness of monetary and fiscal policy in China with a shadow banking sector. We develop a dynamic stochastic general equilibrium (DSGE) macroeconomic model with two production sectors, where the SOEs have access to low cost funds from the commercial banks (also mainly state‐owned) and on‐lend to the private sector in the form of entrusted loans. The Bayesian estimation results show that higher restrictions on bank credit push SOEs to engage in more shadow banking in this form which dampens the effectiveness of contractionary monetary policy. Expansionary fiscal policy increases output, but crowds out private investment, which can further drain the financial market and exert a detrimental effect on the Chinese economy.